Progressive methods of teaching history at school level in Swaziland: teachers' perceptions of what is essential to their classroom practices - Nsibande, Rejoice Ncamsile (My University, 2014)
The primary aim of the study, is to investigate teachers’ views about what is necessary for the effective use of progressive methods in the teaching of history. It argues that the mere adoption of procedures associated with progressive methods in teaching without awareness of the essentials for using them' does not lead to the expected results. The study draws its research from two high schools in the Manzini Region in Swaziland, and concludes that even though teachers were using a terminology of progressive methods when talking about their teaching strategies, they were unaware of the essential skills related to such terminology, anJ subsequently could not encourage the development of such skills. Their understanding of the nature of history as a discipline and its value as a school subject is also identified as limited. The study recommends that for teachers to overcome these shortcomings, they need to be part of the discourses that defines their discipline and the discussions on what is essential for the teaching of history.